Experiences of HIV Positive Serostatus Disclosure to Sexual Partner Among Individuals in Discordant Couples in Mbarara City, Southwestern Uganda. - Atwijukiire, Humphrey; Nakidd, Gladys; Tweheyo, Otwine Anne; Kabami, Jane (Kabale University, 2024)
Purpose: Disclosure of HIV status is key in HIV management. Despite many studies on serostatus disclosure, there is a gap in experiences regarding HIV status disclosure among discordant couples. The current study addressed this research gap and explored the lived experiences of serostatus disclosure among discordant couples in Mbarara City, South Western Uganda. Participants and Methods: We conducted 12 in-depth interviews with the help of a translated interview guide, and they were audio recorded. Participants were purposively enrolled in the study, which employed a phenomenological qualitative design. The study was conducted at three public health facilities in Mbarara City. The data was analyzed using thematic content analysis. Approval for this research was obtained from the Mbarara University Research Ethics Committee (MUST-REC) and administrative clearance from the city clerk of Mbarara City. Results: The mean age of the participants was 38 years old, ranging from 20 to 67 years. An equal number of males (six) and females participated in this study. Most of them had at least secondary level education, and only three had primary education. Half of the participants disclosed their serostatus to partners immediately after testing HIV positive. Key emerging themes as experienced benefits of HIV serostatus disclosure included: 1) social support and care; 2) decisions regarding health, fertility, and childbearing; 3) sharing information on HIV prevention and protection measures; 4) positive living; and 5) ease of HIV serostatus disclosure. The challenges associated with serostatus disclosure were summarized as one theme: misunderstandings in the families of the discordant couples. Conclusion: Socially, psychologically, and financially HIV positive individuals have benefited from their negative partners. Healthwise, they have been supported and cared for after disclosing their positive status, but some have faced challenges, such as family misunderstandings. Couple HIV counseling and testing by a trained health worker is beneficial in HIV care and could mitigate the challenges related to HIV serostatus disclosure.